Cholesterol-dependent attachment of human respiratory cells by Bordetella pertussis - Lamberti, Yanina Andrea (2009)
Bordetella pertussis is a re-emerging human respiratory pathogen whose infectious process is not fully understood, hampering the design of effective vaccines. The nature of bacterial attachment to host cells is a key event in the outcome of the infection. However, host cell receptors involved in B. pertussis colonization of the respiratory tract are still under investigation. Here, we report that cholesterol-rich domains are involved in B. pertussis adhesion to epithelial cells. Treatment of A549 cells with cholesterol-sequestering drugs such as methyl-β-cyclodextrin, nystatin, or filipin resulted in a significant decrease of B. pertussis attachment. Confocal laser microscopy studies showed B. pertussis associated with cholesterol-rich domains. Accordingly, B. pertussis was found in detergent-resistant membrane domain fractions isolated from bacterial-infected A549 cells. Our results indicate a main role of filamentous hemagglutinin, an environmentally regulated virulence factor, in this interaction, and a specific affinity for cholesterol, one of the major components of traqueal secretions, which might additionally contribute to the effective colonization of the respiratory tract.